DETECTION OF THE ANTIBACTERIAL EFFECT OF NIGELLA SATIVA GROUND SEEDS WITH WATER - Bakathir, H.; Abbas, N. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Nigella Sativa (NS) seeds have been used for medicinal purposes for centuries both as herbs and its oil. In Islam it is regarded as one of the greatest forms of healing medicine included in the medicine of prophet Mohammed. Huge number of studies have been carried out in recent years on the pharmacological effects of these seeds and also the possible relationship with their constituents. A number of these investigations emphasized the antimicrobial effect of them by using different extracts. In our study we have tried to use the normal human mechanism in digestion by using the ground seeds. A modified paper disc diffusion method was used to test the antibacterial effect of NS seeds. Clear inhibition of the growth of Staphylococcus aureus was observed by concentration of 300mg/ml with distilled water (D.W.) as control , this inhibition was confirmed by using the positive control Azithromycin. The inhibition obtained was higher with Nigella sativa ground seeds from Hadramout (HNSGS) than with Nigella sativa ground seeds from Ethiopia (ENSGS). No inhibition was found in the growth of E.Coli and Enterobacter. This was emphasized by using the positive control Ciprofloxacin. The positive inhibition may be attributed to the two important active ingredients of NS, Thymoquinone and melanin .